Reinforcing collectiveness in entrepreneurial interactions within start-up teams: a multiple-case study. Issue 9 (20th October 2019) - Forsstrom-Tuominen, Heidi; Jussila, Iiro; Goel, Sanjay
ABSTRACT: Using a qualitative multiple-case study approach and data from four high-technology team startups, we elaborate a theory on organizing entrepreneurial actions as team efforts and the kinds of interactions that reinforce collectiveness amongst entrepreneurial teams. Through systematic thematic analysis, we find that entrepreneurial action reinforces collectiveness through and during (a) the joint analysis and planning of entrepreneurial opportunities and strategies, (b) the joint decision-making and realization of opportunities and (c) the evaluation, feedback and sanction of entrepreneurial action. We analyse the dimensions through Giddens's ideas on the duality of structures and agencies. We identify interactions that reflect a joint elaboration of opportunities, open and continuous sharing of knowledge and feelings, equality and democracy, joint effort and credit, informality and lack of bureaucracy, and feedback and helping. Our insights could be applied to create collectively entrepreneurial teams and to design education and training activities at a macro level to enable regional development.